Bibliometric Analysis of Innovation and Sustainability in Health Tourism: Analisis Bibliometrik Inovasi dan Keberlanjutan dalam Wisata Kesehatan - Erwin, Erwin; Paputungan, Irving Vitra (Indonesian Journal of Innovation Studies, 2025)
General Background – Health tourism is a rapidly expanding industry driven by innovation and digital transformation, offering high-quality and cost-effective healthcare solutions globally. Specific Background – Despite its growth, there is limited research on the integration of digital technologies such as telemedicine, artificial intelligence, and blockchain in enhancing patient experience and operational efficiency. Knowledge Gap – Previous studies have primarily focused on infrastructure, patient motivation, and service quality, leaving a gap in understanding the role of digital transformation in health tourism. Aims – This study aims to analyze trends in health tourism innovation, mapping technological advancements, policy adaptations, and business model transformations using bibliometric analysis. Results – Findings indicate that digital health solutions, particularly telemedicine and Electronic Health Records (EHR), significantly enhance accessibility and service quality. Future research should focus on data-driven technologies and sustainable business models. Novelty – This study contributes by systematically mapping digital innovations in health tourism through bibliometric analysis, offering a comprehensive perspective on the industry's evolution. Implications – The findings provide strategic insights for policymakers and industry stakeholders, emphasizing the importance of standardized business process modeling to enhance service efficiency and competitiveness in global health tourism markets. Highlights:  Digital Transformation in Health Tourism – The integration of telemedicine, AI, and blockchain enhances patient experience, accessibility, and service efficiency. Bridging the Knowledge Gap – This study fills a research gap by systematically mapping digital innovations in health tourism through bibliometric analysis. Strategic Implications – Findings provide actionable insights for policymakers and industry leaders to standardize business processes and improve global competitiveness. Keywords: Health Tourism, Development, Innovation